Virtual screening campaigns and ADMET evaluation to unlock the potency of flavonoids from Erythrina as 3CLpro SARS-COV-2 inhibitors - Vicki Nishinarizki, Ari Hardianto, Shabarni Gaffar, Muchtaridi Muchtaridi, Tati Herlina (Journal of Applied Pharmaceutical Science, 2023)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused the coronavirus disease 2019 (COVID-19) pandemic with more than 6 million deaths worldwide. Flavonoids from the genus Erythrina may inhibit SARS-CoV-2, targeting 3C-like protease (3CLpro), an enzyme essential in the virus’s growth. Hence, this study aimed to screen 378 flavonoids from Erythrina against 3CLpro, using molecular docking, Lipinski’s rule of five, and in silico absorption, distribution, metabolism, excretion, and toxicity. These virtual screening campaigns suggest that 108 flavonoids have stronger binding energy values (−13.23 to −10.20 kcal/mol) than the N3 inhibitor (−10.14 kcal/mol) as the reference ligand. Some 33 of these flavonoids may be hepatoxicity- and mutagenicity-free. They are also non-hERG I and II inhibitors. Two of them, orientanol E (171) and erycaffra F (57), have binding energy values in the top 10 hits and good absorption profiles, despite their poor distribution properties. They may have a high bioavailability in the body and be excreted from the body through feces. Conducted molecular dynamics simulations also support orientanol E (171) and erycaffra F (57) as 3CLpro inhibitor candidates. Our study suggests that flavonoids from Erythrina have the potential as 3CLpro inhibitors, which help guide further in vitro and in vivo experiments in COVID-19 drug development.